Implementation of Iot-Based Smart Farms for Optimizing Chicken Productivity and Product Digitalization to Improve Administration Quality - Alita, Debby; Samsugi, Slamet; Suhadi, Miki (STKIP Singkawang, 2023)
Lampung People Berjaya is one of the visions of the Lampung provincial government to fulfill conditions of safety, advanced culture, competitiveness and prosperity, so that to achieve this the government has one target, namely to move the agricultural and livestock sectors in Bumi Ruwai Jurai so that Lampung can become an agricultural locomotive. and livestock barns. Berkah Poultry Farm (BUF) is a broiler and stud chicken farm located in Jati Agung, South Lampung. The main problems that are a priority to be resolved are: 1) The temperature and humidity control device for the cage is still semi-automatic; 2) Management of daily livestock data is still done manually; 3) There is still low understanding of breeders and their employees regarding chicken farming. Based on the priority problems faced by partners, the solutions offered by the proposing team for this PKM scheme are: 1) Implementing Smart Farm: IoT-based Automatic Temperature and Humidity Control Device; 2) Implement Smart Farm: Web-based livestock data management application; 3) Providing educational training on livestock cultivation for breeders and all BUF employees. The results of this service are an increase in the ability of Berkah Unggas Farm employees as evidenced by pretest and posttest results, increased chicken productivity as evidenced by increased chicken weight and more accurate data reports on consistent temperatures.